The deadliest creature in the world - Guiberson, Brenda Z. (Henry Holt and Company, 2016)
Which creature is the deadliest? Is it the insect that bites, the ostrich that kicks, the snake that squeezes, or the shrew that paralyzes? Is it the most venemous, the most poisonous, or the one that infects its victims with a fatal disease? Fascinating facts and spectacular illustrations will inspire young readers to choose which creature they think is the deadliest in this newest picture book collaboration between Guiberson and Spirin. --Publisher